Peran Komite Sekolah dalam Mengimplementasikan Manajemen Berbasis Sekolah pada Lingkup Yayasan Pembinaan Pendidikan Kristen Dr. J. B. Sitanala Cabang Masohi Maluku Tengah 2023 - Sartje Augustyn; Izaak HendrikWenno; L. J. Lokollo (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The purpose of this research is to analyze the role of the school committee in YPPK Dr. J. B. Sitanala Masohi Branch in implementing SBM, as well as analyzing what supporting and inhibiting factors were faced by the school committee within YPPK Dr. J. B. Sitanala Masohi Branch in implementing SBM. This type of research is field research, using a qualitative research approach to analyze and describe the implementation of SBM in schools within the scope of YPPK Dr. J. B. Sitanala Masohi Branch. The research took place in 5 schools under YPPK Dr. J. B. Sitanala Masohi branch, in March-May 2023. The research data was obtained using observation, interview and documentation techniques. Data analysis uses the Miles and Huberman method. Based on the results of the research, the conclusion that can be drawn is the role of the school committee in YPPK Dr. J. B. Sitanala Masohi branch in implementing SBM as an Advisory agency is on a fairly good priority scale (60%), Supporting agencies are on a good priority scale (70%), Controlling agency is on a the priority is quite good (45.71%), and the Mediator agency is on a good priority scale (73.3%). Factors inhibiting school committees in the scope of YPPK Dr. J. B. Sitanala Masohi Branch in implementing SBM, namely the quality of school committee human resources, an incorrect understanding of the role of school committees, the public's perception of free education is still wrong, the distribution of educators by the Government, as well as the socio-economic background of students' parents.